Biologia e sucesso reprodutivo de coccyzus melacoryphus (aves: cuculidae) em uma área de Caatinga - Paixão, Victoria Helen Figueiredo (2019)
Studies on the reproductive dynamics of birds in seasonal environments have been mainly focused in temperate regions generating a knowledge gap for neotropical regions. Basically, our knowledge about birds’ history life theory is based on the comparison of the strategies observed between temperate and tropical humid areas. However, studies in seasonal tropical regions, such as caatinga, are important to better understand the evolutionary patterns. This research aims at increasing our understanding about the reproductive dynamics of birds from seasonal environments, describing aspects of The Dark-billed Cuckoo’s (Coccyzus melacoryphus) breeding biology: reproductive period, nest and egg description, posture size, incubation and nesting period. C. melacoryphus belongs to the Cuculidae family, which occurs throughout Brazil. It performs periodic movements in part of its distribution. In Rio Grande do Norte state, its permanence period is related to the rainy season, occurring between February and June when they arrive to breed. We conducted the study at the “Estação Ecológica do Seridó” during the rainy season of 2017 and 2018 (January to June) where we performed active nest searches. We monitored nests at 2-3 days intervals. We recorded 63 nests, which 31 nests were monitored between March 1 and May 8 of 2017, and 32 nests between February 8 and June 10 of 2018. The nests were built on shrubs and trees with 1.61 ± 0, 88 m mean height, and the pereiro tree (Aspidosperma pyrifolium) was the main plant used as support. The nests showed a “simple/platafform” format, with sticks showing a tendency to present the outer ones larger in length and diameter than the inner ones. The eggs were short subelliptical with light green coloration (color 81 Pearl Gray by Smithe 1975). Clutch size varied from one to six eggs. The eggs mean weight was 9.7 ± 0.9 g, the length was 28.4 ± 1.5 mm and width was 22.1 ± 1.5 mm. The mean nestlings number per nest was 2.60 ± 0.96 (n = 32). In its breeding biology, we believe that C. melacoryphus behaves like the other members of the genus, presenting a longer reproductive period when compared to birds of temperate regions, with a probable short incubation period and nestlings’ permanence. However, clutch size of up to six eggs was contrary to that expected from tropical birds.